Propagação de rambutanzeiro (Nephelium lappaceum L.) por enxertia - Barreto, Lívia Felício; Cavallari, Ludmilla De Lima; Venturini, Guilherme Costa [UNESP]; De Andrade, Renata Aparecida [UNESP]; Martins, Antonio Baldo Geraldo [UNESP] (My University, 2015)
There is great genetic diversity of rambutan plants, thus, to establish commercial orchards cul-ture, it is recommended the use of plants vegetatively propagated. Therefore, this research aimed to determine the best method of grafting, graft protection and type of rootstock for its propagation. The experiment was re-peated in two seasons (autumn/winter and spring/summer). The experimental design was completely random-ized in both experiments, with four replicates, each experimental unit consisted of 10 plants analyzed in a 4x2x2 factorial with four types of grafting (whip graft-WG; cleft graft –CG; wedge graft-WG; and inverted wedge graft-IWG;), 2 types of graft protection (Biodegradable and plastic) and 2 types of rootstock (without or with leaves). The variables analyzed in this study were: percentage of grafting success, number and length of buds (cm). For grafting performed in autumn / winter, both by cleft grafting as whip graft with biodegradable strip and rootstock leafless provided the best results in propagation of rambutan tree. The best results were ob-served during the autumn / winter.
Propagation of rambutan tree (Nephelium lappaceum L.) for grafting
Keywords: Graft protection; Grafting; Nephelium lappaceum L; Rootstock